1993
DOI: 10.1182/blood.v81.5.1132.1132
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-alpha in mixed cryoglobulinemia patients: a randomized, crossover-controlled trial

Abstract: The effects of interferon-alpha (IFN-alpha) on clinical and serologic manifestations of mixed cryoglobulinemia (MC) were investigated by randomized, crossover-controlled trial in 26 patients. The trial alternated 6 months with and 6 months without IFN-alpha therapy (2 x 10(6) IU daily for a month, then every other day for 5 months). In 22 patients, pretreatment steroid dosage remained unchanged during the study. Six patients dropped out (three because of side effects), whereas another 20 patients experienced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
5

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(63 citation statements)
references
References 26 publications
2
56
0
5
Order By: Relevance
“…Interferon-a has been shown to be clinically ef®cacious in the management of HCV-associated MC in several large randomized studies. 6 Unfortunately, our patient falls into the worse prognostic group with high viral load (> 2´10 6 HCV copies ¤ mL blood), genotype I, more than 40 years of age, and evidence of liver ®brosis. Other reasons for treatment failure in this case may be due to the delay in reaching a ®nal diagnosis due to false-negative serology and inadequate duration of treatment (6±12 months minimum).…”
Section: Discussionmentioning
confidence: 84%
“…Interferon-a has been shown to be clinically ef®cacious in the management of HCV-associated MC in several large randomized studies. 6 Unfortunately, our patient falls into the worse prognostic group with high viral load (> 2´10 6 HCV copies ¤ mL blood), genotype I, more than 40 years of age, and evidence of liver ®brosis. Other reasons for treatment failure in this case may be due to the delay in reaching a ®nal diagnosis due to false-negative serology and inadequate duration of treatment (6±12 months minimum).…”
Section: Discussionmentioning
confidence: 84%
“…Early studies using IFN monotherapy showed that, in spite of a clinical-immunological response during treatment, both infection and vasculitis generally relapsed after treatment. [32][33][34][35] The MC response improved with the increased efficacy of antiviral therapy, passing from recombinant IFN 32 to PEG-IFN plus RBV. This latter combination, in some studies, was able to lead to a clinical response ranging from 62.5% to 78% of patients, 17,36 suggesting that it should be the first therapeutic option for patients with HCV-MCS.…”
Section: Discussionmentioning
confidence: 99%
“…60 IFN-a monotherapy achieved SVR in 4%-27% of patients with HCV-MCS and a moderate complete clinical response rate of 27%-62%. 58,59,[61][62][63] The combination of pegylated IFN-a with RBV is more efficacious, resulting in SVR rates of 18%-54% and complete clinical response rates of 44%-77%, although relapse rates are still as high as 60%, and because of this improvement in renal manifestations is only seen in 50%. 45,[63][64][65][66][67] Patients whose HCV relapses after IFN-based treatment typically have recurrence of HCV-MCS symptoms.…”
Section: Antiviral Therapy: Historical Use Of Ifn and Ribavirin In Hcmentioning
confidence: 99%